Pengembangan Sistem Informasi Manajemen Pendidikan Dan Pelatihan (Diklat) Pendidik Dan Tenaga Kependidikan (Studi Kasus : LPMP Sulawesi Tenggara) - Muhammad Ednan Fajri Gunadi; Satrio Agung Wicaksono; Fajar Pradana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Lembaga Penjaminan Mutu Pendidikan (LPMP) of Southeast Sulawesi is a technical implementation unit with the task of undertaking quality assurance of primary and secondary education in the province. To carry out these tasks LPMP Southeast Sulawesi conduct training activities which in its implementation get some problems. The first problem is the registration process is done manually so that the pile of queues of prospective participants. The second problem, the data processing is done centrally so it takes additional time to perform data processing. Third problem, the dissemination of information done manually so as to affect the performance of the committee. The fourth problem is the submission of participant certificates that are often lost or tampered. Based on these problems, the solution is to develop a management information system developed using throw-away prototype method. Throw-away prototype method is chosen because by using the method can understand the needs of users in the early stages thereby reducing the risk of system failure. The results of this study, obtained 1 iteration that produces 34 functional requirements, and 1 non-functional needs. Based on the results of validation testing found that all functions can run well with valid status results. Based on the results of compatibility testing found that in the Safari browser version 11 and below, Opera version 47, Google Chrome version 61 and IOS System version 11 and below no problems found. Based on UAT test results, it is found that all tested functions can be accepted by the user.